Continuous catalytic coupling of raw bioethanol into butanol and higher homologues. (15th October 2015) - Dziugan, Piotr; Jastrzabek, Konrad G.; Binczarski, Michal; Karski, Stanislaw; Witonska, Izabela A.; Kolesinska, Beata; Kaminski, Zbigniew J.
Graphical abstract: Highlights: Condensation bioethanol was successfully performed over 8–20%Ni/Al2 O3 catalysts. 20%Ni/Al2 O3 yielded almost 13% butanol after a single passage of bioethanol at 330 °C, 120 atm. The use of a two-zone reactor allowed the system to operate under milder pressure (80 atm) and temperature (290 °C) condition. The results of the studies suggest the possibility of using continuous-flow technologies for the industrial-scale. Abstract: Continuous catalytic condensation of crude distillates or rectified bioethanol into butanol and other fuel bicomponents was performed over 8–20%Ni/Al2 O3 catalysts. Experiments were conducted using solid catalysts in a flow reactor under supercritical conditions. The most promising nickel catalyst yielded almost 13% butanol after a single passage of the raw spirit or rectified ethanol at 330 °C, 120 atm. The butanol content in the liquid products was further increased to 31.4% (v/v) by the additional step of rectification and recycling of the low-boiling fraction through a catalytic reactor. The use of a two-zone reactor filled with different catalytic systems (I. 8%Ni/Al2 O3 ; II. 5%Pd-8%Fe/Al2 O3 ) allowed the system to operate under milder pressure (80 atm) and temperature (290 °C) conditions, while maintaining approximately 13% (v/v) of the butanol content in the reaction mixture. The results of the studies suggest the possibility of using continuous-flow technologies for the industrial-scale catalytic condensation of bioethanol into butanol and higher homologues, which are valuable fuel biocomponents.